Reporting of Randomized Controlled Trials Investigating an Enteral or Parenteral Nutrition Intervention in Critical Illness According to the CONSORT Statement: A Systematic Review and Recommendation of Minimum Standard Reporting Criteria. Issue 3 (21st November 2020) - Seddon, Nathan; Chapple, Lee‐anne S.; Tatucu‐Babet, Oana A.; Ridley, Emma J.
Abstract: Lack of reporting consistency is common in randomized controlled trials (RCTs) in critical care nutrition. This impacts synthesis and interpretation and may misinform clinical practice. The objective was to evaluate reporting of parallel‐group RCTs of enteral or parenteral nutrition interventions in critically ill adults against the recommendations in the Consolidated Standards of Reporting Trials (CONSORT) 2010 guidelines and a priori–defined nutrition criteria. A systematic search of CENTRAL, MEDLINE, EMBASE, and CINAHL was conducted to identify RCTs published from January 2011 to February 14, 2020. The primary outcome was the percentage of CONSORT criteria "completely met" (a score of 1) from all included studies (out of a total possible score of 37). Secondary outcomes included the percentage of CONSORT criteria that were "partially" or "not met" and the percentage of a priori–defined nutrition criteria that were "completely, " "partially, " or "not met" (adjusted to reflect criteria applicable to the paper). Data are presented as mean (standard deviation). Comparisons of normally distributed continuous data were made using a t ‐test ( P < .05). Of 18, 969 articles identified, 56 studies met inclusion criteria. Of these, 60% (19%) of the eligible CONSORT criteria were "completely met, " 20% (9%) "partially met, " and 20% (15%) "not met." For the nutrition criteria, 41% (20%) of the eligible criteria were "completely met, " 25% (14%) "partially met, " and 34% (17%) "not met." Reporting against CONSORT guidelines was variable and often incomplete in relation to important a priori–defined nutrition variables.